Glaucoma progression during the COVID-19 pandemics - V.E. Korelina; I.R. Gazizova; A.V. Kuroyedov; M.D. Didur (РМЖ "Клиническая офтальмология")
V.E. Korelina1, I.R. Gazizova2, A.V. Kuroyedov3,4, M.D. Didur2 1LLC “American Medical Clinic”, St. Petersburg, Russian Federation 2N.P. Bekhtereva Institute of the Human Brain, St. Petersburg, Russian Federation 3P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation The novel coronavirus infection (COVID-19) provides powerful effects on all pathogenic aspects of the primary open-angle glaucoma (POAG). The property of this virus to initiate disseminated intravascular coagulation, damage endotheliocytes, and impair coagulation result in numerous severe complications affecting all organs and systems. This disorder provokes retinal ischemia and hypoxia and spurs apoptosis of ganglionic cells. Cytokine storm and oxidative stress resulting from the COVID-19 potentially contribute to the progression of glaucomatous optic neuropathy. Distressing effect of the pandemic, a growing number of patients with depressive and anxiety disorders increase the risk of POAG and ocular hypertension, reduce treatment compliance, and exacerbate glaucoma course. Ophthalmic patients should be informed on potential risks and consequences of the COVID-19 and educated on the safety and efficacy of vaccination and the need for these preventive measures for elderly patients (in particular, with glaucoma). A year of the COVID-19 pandemic has radically changed the attitude to many processes  of doctor-patient relationships. There is a need for the development of the technologies of distant monitoring of patients with glaucoma. Keywords: primary open-angle glaucoma, COVID-19, telemedicine, pandemic, SARS-CoV-2, cytokine storm, oxidative stress, intraocular pressure, apoptosis of ganglionic cells, glaucomatous optic neuropathy, post-COVID-19 syndrome. For citation: Korelina V.E., Gazizova I.R., Kuroyedov A.V., Didur M.D. Glaucoma progression during the COVID-19 pandemics. Russian Journal of Clinical Ophthalmology. 2021;21(3):147–152 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-147-152.